Reader's identity construction of the portuguese "carnation revolution" (1974) in the anglo-portuguese news - mattos-parreira, merja (2013)
"Identity" and "identity crisis" are terms and ideas much in current use in cultural studies of the 1990's and often seen as characterising contemporary societies. According to Stuart Hall, identities are built within discourse cognitively and through difference rather than through a combination or play of association.